Geometric and numerical optimisation of single- and two-phase convective heat transfer in microchannel heat sinks - Ariyo, David Olugbenga (Department of Mechanical Engineering, 2025)
Innovative and efficient cooling systems are required for the present and future high heat flux applications because natural and forced air convection and many other cooling methods employing liquid coolants cannot meet up with the challenges. More transistors are added to the surfaces of electronic chips to increase the capacity of integrated circuits and more heat is generated; hence a better cooling method is highly desirable. A cooling system should be designed in such a way that pressure drop is minimised while maximising thermal performance at low thermal resistance and temperature. To satisfy high heat flux demand and compact size for the present and future applications, single-phase and two-phase convective heat transfer mechanisms in circular, equilateral triangular, rectangular and square microchannels (micro passages for liquid flow in the heat sinks) were studied to enable electronic chip manufacturers to produce more powerful and durable integrated circuits at temperatures well below the recommended highest operating temperature. There is the need to optimise different microchannel configurations for low, medium and high heat fluxes at moderately low velocities and pressure drops with the aim of having optimal microchannel heat sinks that perform well in two-phase and single-phase flow and at low pumping power. Also, the problem of instability has to be solved by having optimal and stable microchannel heat sinks. In operation, microchannel heat sinks could be used beyond their optimal limits, hence specification of maximum permissible heat fluxes (critical heat fluxes) is necessary. Deionised water was used as the working fluid because of its thermal advantage (high thermal conductivity, high specific heat), availability and environmental friendliness compared to other fluids like refrigerants. Aluminium was used as the heat sink material because of its light weight, low cost, ease of fabrication and relatively high thermal conductivity. Copper was used as the heat sink material for high heat flux study (800 to 1200 W/cm2) in rectangular microchannel heat sinks solely because of its high thermal conductivity. Simulation and optimisation studies of two-phase and single-phase convective heat transfer in microchannels are limited considering the way they have been done presently. Goal driven optimisation was used and the volumes of microchannels and heat sinks were fixed over a wide range of heat fluxes and velocities. Geometric optimisation and flow parameters modelling were studied for subcooled flow boiling (two-phase flow) in horizontal circular, equilateral triangular, rectangular and square microchannels to solve the problem of high heat flux dissipation in microelectronic devices and other similar applications. The four microchannel heat sink configurations presented for simulations and optimisations were considered to be good designs after being tried in single-phase and two-phase flow simulations. The objective was to minimise the thermal resistance of microchannel heat sink at each velocity range and fixed heat flux subject to fixed volume constraints of the heat sink and microchannel. Manufacturing constraints were also applied to ensure reliability in practical applications. Geometric and numerical optimisation was carried out to determine the optimal shapes of microchannel heat sinks and the optimal numerical values of flow parameters. The geometric and flow parameters were allowed to morph to obtain their optimal values. Highly subcooled deionised water at inlet temperature of 25 oC (degree of subcooling being 75 oC) was used as the cooling fluid and aluminium as the heat sink material for heat fluxes up to 700 W/cm2. For high heat flux study (800 to 1200 W/cm2), deionised water at inlet temperature of 10 oC (degree of subcooling, 90 oC) was used and copper was the heat sink material. Velocities from 0.1-0.5 to 6.5-7.0 m/s and heat fluxes between 100 and 1200 W/cm2 (1x106 W/m2 and 1.2x107 W/m2) were considered in the modelling and optimisation procedures. Computational fluid dynamics (CFD) code, ANSYS (heat flux partitioning model and goal driven optimisation tool) was used for the simulations and optimisations of the microchannel heat sink configurations. The numerical code used for the simulations in two-phase flow was validated by the available experimental data in the literature and the agreement showed the capability of CFD (ANSYS) to predict accurately, subcooled flow boiling (two-phase flow) in the microchannels for cooling of microelectronic devices. Single-phase flow validation was also done with the available experimental data in the open literature and the agreement was good. Grid refinements were done for the initial designs of microchannel heat sink configurations presented for simulations and optimisations to achieve grid independent results. In two-phase flow, optimal results were obtained for rectangular microchannel heat sinks for all the heat fluxes considered while for the remaining microchannel heat sinks, results could only be obtained up to the maximum of 500 W/cm2 for equilateral triangular microchannel heat sinks and 400 W/cm2 each for circular and square configurations. Two-stacked and v-grooved rectangular microchannel heat sinks were used to achieve the maximum heat flux of 1200 W/cm2. In single-phase flow, optimal results were obtained up to 200 W/cm2 for circular and rectangular microchannel heat sinks while for equilateral triangular and square configurations,results were obtained at 100 W/cm2 only, due to high base (bottom) temperatures. Comparisons were made between two-phase and single-phase flow by using their optimal geometric and flow parameters, and the results clearly demonstrated the superiority of two-phase flow regime in all the microchannels, for removal of high heat fluxes at low Reynolds numbers. The pumping power requirements for optimal microchannels were compared and considered useful in practical applications such as in the cooling of electronic devices. Contours are provided to show wall temperature distribution for the heat sinks, water and water vapour in the microchannels. Using non-equilibrium subcooled boiling model which is an extension of heat flux partitioning model, critical heat fluxes for optimal microchannel heat sinks at velocities in the range 2.0-2.5 to 3.5-4.0 m/s and 100 W/cm2 were computed, to demonstrate that optimal microchannel heat sinks could be operated beyond the heat fluxes for which they had been optimised. Multichannels of optimal microchannel heat sink configurations were compared over a width of 1 cm which is common in electronic packaging and rectangular microchannel heat sinks had the best thermal performance while circular configuration had the least performance in subcooled flow boiling. For the four microchannel configurations considered, an array of optimal microchannel heat sinks that performed well in two-phase and single-phase flow, one-stacked and two-stacked in parallel flow and counterflow arrangements, has been achieved at high heat fluxes not reported in open literature for similar geometries, for cooling of electronic devices and in other applications. Stability of optimal results was ensured in the simulations and optimisations, and in the critical heat flux computations.